A perinatal health framework for women with physical disabilities. Issue 4 (October 2015) - Mitra, Monika; Long-Bellil, Linda M.; Smeltzer, Suzanne C.; Iezzoni, Lisa I.
Abstract: Background: Studies suggest that women with disabilities experience health and health care disparities before, during, and after pregnancy. However, existing perinatal health and health care frameworks do not address the needs and barriers faced by women with physical disabilities around the time of pregnancy. A new framework that addresses perinatal disparities among women with physical disabilities is needed. Objective: To propose a framework for examining perinatal health and health care disparities among women with physical disabilities. Methods: We developed a perinatal health framework guided by the International Classification of Functioning, Disability and Health (ICF) and the integrated perinatal health framework by Misra et al. Results: The proposed framework uses a life span perspective in a manner that directly addresses the multiple determinants specific to women with physical disabilities around the time of pregnancy. The framework is based on longitudinal and integrated perspectives that take into account women's functional status and environment over their life course. Conclusion: The perinatal health framework for women with physical disabilities was developed to inform the way researchers and health care professionals address disparities in perinatal health and health care among women with physical disabilities.